Pendekatan Pengawasan Internal dalam Pencegahan Fraud: Peran Moderator Audit Intern - Iman Kadarman; Meiliani Meiliani; Arif Santoso (Ilmiah Manajemen Bisnis, 2019)
Abstract — The phenomenon of fraud in the government becomes a challenge for the effectiveness of internal control to reduce the risk of the threat. Since COSO identifes informal and formal aspects within the framework of the internal control, soft control and hard control are two internal control approaches that need to be applied. The presence of the internal audit is a function that cannot be ignored in strengthening the internal control system. This study aimed to investigate the role of internal audit of the effect of soft control and hard control on the fraud prevention of fnancial statements in the Local Government of Bengkulu City. One hundred and forty-fve fnancial management offcials at OPD Bengkulu City were surveyed. The results of data analysis show that (1) the soft control partly has a signifcant effect on the fraud prevention, only on the commitment on competence, and the responsibility and authority delegation; (2) the hard control partly and signifcantly inﬂuences the fraud prevention only on the performance review, the information system control, and the documenting; (3) the internal audit moderates partly the effect of the soft control on the fraud prevention only on the commitment on competence, the responsibility and authority delegation; the assurance activity, the consulting activity, the commitment on competence and assurance activity, and positive leadership and the assurance activity; and (4) the internal audit partly moderates the effect of the hard control on the fraud prevention on the performance review, the information system control, and the. Discussion and implication are discussed. Keywords— Financial statement, Fraud, Hard control, Internal audit, Soft control